Aswaja In Higher Education as A Former of Social Character in The Perspective of Islamic Education - Kodijah, Siti; Ulya, Fina; Afwullah, Muhammad (AL-WIJDÃN Journal of Islamic Education Studies, 2025)
ASWAJA courses in higher education are not only taught in the PTNU environment, but also in various other tertiary institutions belonging to the Ahlussunnah wal Jama'ah sect. This research is motivated by indications that the ASWAJA course is starting to be separated from its social-historical roots. The objective of this research is to explore the extent to which the ASWAJA course in tertiary institutions aligns with the vision of higher education and the needs of contemporary society. To this end, a qualitative approach is employed to investigate how ASWAJA is taught in universities and its relevance in addressing socio-religious issues. The objective of this research is to ensure that the ASWAJA course does not become utopian but rather provides students with a contextual understanding of the evolving dynamics of society. This article employs a qualitative approach, utilizing documentation and interview techniques, and the theoretical framework is drawn from the sociology of knowledge as developed by Karl Mannheim. The research findings indicate that, firstly, the ASWAJA course at the research site remains utopian and is incapable of fully integrating ASWAJA values with social reality. Secondly, to optimize the contribution of ASWAJA learning to the shaping of student character in a heterogeneous society, an approach is required that incorporates three aspects: intelligence questions, emotional questions, and spiritual questions. This approach is expected to strengthen students' understanding of ASWAJA in a more comprehensive, contextual, and applicable manner in social life: intelligence questions, emotional questions, and spiritual questions.   Keywords: Aswaja; NU; Social Character; Sociology Mannheim